Implementation of Law on Pension Provision for Collective Farmers in Sverdlovsk Region (1964-1965) - V. N. Mamyachenkov; V. V. Shvedov; Y. L. Ponomarev (Научный диалог)
The article is devoted to the problem of pension provision of collective farmers in the USSR. The study was conducted on archival materials with the involvement of Internet sources, as well as scientific and reference literature. The relevance of the topic is determined by its importance for the social sciences, especially for history, sociology and economics. The scientific novelty of the work is seen in the fact that new materials discovered by authors in the funds of these archives are introduced into circulation. The time frame of the article - 1964 and 1965 - is determined by the fact that in this period the state pension provision of collective farmers was introduced. It is claimed that the salaries charged to collective farmers were several times less than the salaries of the majority of urban residents. It is stated that the introduced pensions only to a small extent facilitated the financial situation of the collective farm peasantry. It is claimed that almost all the surveyed collective farmers-pensioners were set a minimum pension. It is proved that the size of disability pensions for farmers initially could not be high. It is concluded that the attitude to the peasantry “on the residual principle” had deep historical roots in the USSR and was based on the well-known concept of Marxist-Leninist theory, which proclaimed the peasantry as a “reactionary” class.